Structural equation model of the relationship between professional ethics and teacher emotions with the mediation of moral identity - Seyfi Fathabadi, Sima; Kamyabi, Mitra; Hajipour Abaei, Najmeh; Manzaritavakoli, Hamdollah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: teachers gain effective experiences of their ethics, capabilities and emotions by using primary and secondary evaluations of the context of the school and classroom. The main goal of the current research was to design a model of professional ethics based on teacher's emotions with the mediating role of moral identity in teachers of Babak city. Method: This research is a descriptive correlation research. The statistical population of this research includes all the teachers of Shahrbabak city, whose number is 1200. From this number, 291 people were selected as the sample size using Cochran's formula. The sampling method used for teachers in Babak city in this research was simple random sampling method. After determining the sample size in each class, simple random method was used to select the sampling unit and 291 people were selected using simple random sampling and the questionnaire was distributed among them. Then, using Armito et al.'s (2011) professional ethics questionnaires, Ghasemi et al.'s (2018) teacher emotions, and Majdabadi's ethical identity (2016) data were collected. Statistical analysis was done using Amos and SPSS software and structural equation model. Findings: The results of the hypothesis analysis showed that the effect of the mediator variable in the regression model is significant and effective. As a result, the main hypothesis of the research that there is a relationship between professional ethics based on teacher's emotions and the mediating role of moral identity in teachers of Babak city is confirmed. Conclusion: Therefore, all the hypotheses of the research are confirmed and finally it can be concluded that there is a positive and significant relationship between the research criteria.